Reconsidering Community Renovation: - Yasunori Miyawaki (Maketingu rebyu)
Effective use of regional resources can have problems when public and private logic intersect, making it difficult to reach a goal. This is because that, in addition to the perspective of utilizing diverse resources within and outside the region, there is a need to take into account the various stakeholders within and outside the region who will be the main actors. In advancing this discussion, we believe that resource integration, which aims to increase the mutual availability of resources from market transactions, private resources, and public resources, is a useful perspective. This study focuses on examples of community renovation that show the effective use of local resources and examines how stakeholders within and outside the region think about their respective roles and the kinds of interactions seen from the perspective of resource integration. As a result, it became clear that resource integration actors within and outside the region not only avoid thinking about the scope of their roles in a fixed manner, but also become the main actors in community renovation by synergistically increasing the availability of the three resources.